Dionysian and Apollonian Portrayed in the movie “Rush”: Psycho-Literature Analysis - Jimmi; Rachman, Claresta Agusty; Sidauruk, Juniato (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The aim of this research is to explain how Dionysian and Apollonian concept is portrayed in the main characters, James Hunt and Niki Lauda, of the movie Rush (2013). This research is a qualitative research method. Researchers choose some scene of the movie Rush, and then continue to classify them into Dionysian and Apollonian concept. Researchers use Porecha theory to analyze the concept of Dionysian that appear in James Hunt character. The Dionysian concept consist of Primary Instinct, Chaos, Connection with Unrestricted Nature, and Rituals. For the Apollonian, researchers use Sharma theory to analyze of apollonian concept that appear in Niki Lauda character. The Apollonian concept consist of order, logic, individual, harmony, structure, and balance. The results reveal for the Dionysian concept found Primary Instinct has 2 data, Chaos has 2 data, Connection with Unrestricted Nature has 2 data, Ritual has 1 data. In Apollonian concept found order has 2 data, Logic has 2 data, Individual has 2 data, Harmony has 2 data, Structure and Balance for each of them have 1 data.